2017
DOI: 10.1016/j.jcjd.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Diabetes Care Quality and Diabetes-Related Hospitalizations and the Modifying Role of Comorbidity

Abstract: Meeting diabetes testing goals has the potential to reduce hospitalizations for diabetes-related complications; however, this depends on types of coexisting chronic conditions and diabetes-related complications in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…For example, Woodard et al confirmed higher achievement of diabetes care goals for glycemic and lipid control in patients with discordant comorbidity only compared with those with diabetes only . Petrosyan et al also showed that either type of comorbidity in patients was associated with meeting diabetes goals of HbA1c testing or low‐density lipoprotein cholesterol testing . These findings could be explained by the frequent interaction of patients with healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Woodard et al confirmed higher achievement of diabetes care goals for glycemic and lipid control in patients with discordant comorbidity only compared with those with diabetes only . Petrosyan et al also showed that either type of comorbidity in patients was associated with meeting diabetes goals of HbA1c testing or low‐density lipoprotein cholesterol testing . These findings could be explained by the frequent interaction of patients with healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…15 Petrosyan et al also showed that either type of comorbidity in patients was associated with meeting diabetes goals of HbA1c testing or lowdensity lipoprotein cholesterol testing. 16 These findings could be explained by the frequent interaction of patients with healthcare providers. In fact, in the present study, patients with comorbidity had almost double the number of physician office visits than those with diabetes only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Appendix 1). [34][35][36][37][38][39][40] We determined the prevalence of any cancer using the OCR. Liver failure and liver transplant were ascertained if one ICD9 or ICD10 code was billed in OHIP or DAD in the previous 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…We also flagged any hospitalization where the most responsible diagnosis was for any of the following chronic physical and mental health ACSCs commonly comorbid with diabetes: obesity (ICD-10-CA codes E66.x), hyperlipidemia (E78.x), hypertension (I10.x-I15.x), ischemic heart disease (I20.x-I25.x), cardiomyopathy (I42.x-I43.x), cardiac arrhythmia (I47.x-I49.x), congestive heart failure (I50.x), stroke (I60.x-I64.x), coronary atherosclerosis (I70.x), thromboembolism (I80.x-I82.x), chronic obstructive pulmonary disease (J41.x-J45.x), chronic kidney disease (N18.x), and polycystic ovarian syndrome (E28.2) as well as mood and anxiety disorders (F30.x-F48.x). While different studies and healthcare organizations use different categorizations of what is considered an ACSC, these conditions have been considered to reflect common coexisting physical and mental health disorders among persons with diabetes relevant for investigations of multimorbidity, care interventions, and preventable hospitalizations [7,8,31].…”
Section: Discharge Abstract Database (Dad)mentioning
confidence: 99%